Smoothed Particle Electromagnetics Modelling on HPC-GRID Environment - Ala, Guido; Francomano, Elisa (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper a meshless approach on a high performance grid computing environment to run fast onerous electromagnetic numerical simulations, is presented. The grid computing and the message passing interface standard have been employed to improve the computational efficiency of the Smoothed Particle Electromagnetics meshless solver adopted. Applications involving an high number of particles can run on a grid computational environment simulating complex domains not accessible before and offer a promising approach for the coupling of particle models to continuous models. The used meshless solver is straightforward to program and fully parallelizable. The results of the parallel numerical scheme are reported and tested on a transverse electric propagation case study taken into account to assess the computational performance.